Analisis kesenjangan kualitas pelayanan pada pt asuransi bangun askrida cabang samarinda - Adji Oktarica Aisyah; Suharno Suharno; Tetra Hidayati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
The purpose of writing this thesis is (1) to find out the level of suitability between the expectations and performance of PT. Asuransi Bangun Askrida Samarinda Branch related to the dimensions of service quality which include tangibles, reliability, responsiveness, assurance, and empathy. which is very important and must be maintained in terms of service quality. (3) to find out whether or not there are real or unreal differences in the treatment before (expectations) and after (reality) from the insured using the services of PT Asuransi Bangun Askrida Samarinda Branch.From the results of the questionnaire distributed to 111 people the results of calculations using the Importance Performance Analysis, the level of suitability for the physical evidence variable, the suitability level is 90.45%. For the reliability variable the suitability level is 87.34%. For the variable responsiveness the level of suitability is 90.40%. For the guarantee variable the level of suitability is 89.23%, and for the empathy variable the suitability level is 91.02%. For processing data using Cartesius diagrams, quadrant A results are 1 factor in the dimensions of reliability and 1 factor in the dimensions of responsiveness where this needs to be improved. Quadrant B is 3 factors in the dimensions of reliability, 2 factors in the dimension of responsiveness; 3 factors in the assurance dimension; and 2 factors for the dimension of empathy where this needs to be maintained, because in general the level of implementation is in accordance with the interests and expectations of its customers. Kudran C is 4 factors from the dimensions of tangibles, and two factors from the dimension of empathy. For quadrant D, none of the research indicators entered into this quadrant. This study also shows that there are significant differences between before and after the insured uses the services of PT Asuransi Bangun Askrida Samarinda Branch, which is shown from the results of paired sample t test from all dimensions of service quality is 0,000.